Pola Komunikasi Guru Akidah Akhlak dalam Pembinaan Moral Siswa MA Pondok Pesantren Raudlatul Jannah - Suhro, Sheila Halimatus; Hadi, Sofyan (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Implementation of learning in educational institutions can not be separated from the role of communication. Different from general communication, communication in education must have clear patterns and not be careless and apply good and correct methods. Research objectives: 1) To describe the communication patterns of aqidah moral teachers in the moral development of MA students at Raudlatul Jannah Islamic Boarding School, 2) To describe the supporting factors and obstacles encountered by teachers in the moral development of MA students at Raudlatul Jannah Islamic Boarding School also related to the problem of communication patterns that use. The research method uses descriptive qualitative with observation, interviews and documentation. The results of the study: the communication patterns carried out include one-way communication patterns, two-way communication patterns and multi-way communication patterns that play an important role in fostering student morals and ethics through the messages conveyed. This is supported by the commitment factor as well as the main vision and written regulations or rules of conduct at the Raudlatul Jannah Islamic Boarding School Islamic Boarding School. While the obstacles to the implementation of the application of communication patterns are: time, adequate and advanced technology, and the absence of Islamic boarding school educational background. At MA Raudlatul Jannah, the application of communication patterns in fostering morals has been running and is realized very well as evidenced by the application of morals in the school environment by students.